Evaluación de la Fermentación de Yuca (manihot esculenta) sometida a tres procesos con Kéfir y Levadura para la Obtención de Bebidas Fermentadas. - Mena Alvarez, Mayuri Yajaira (2019)
The evaluation of the fermentation of cassava (Manihot sculenta) was realized under three processes with kefir and yeast for the production of fermented beverages, it was carried out in order to replace the amylase placed in chewing process to elaborate different gums in an ancestral way. For which an experimental design was carried out with a 3x2x2 factorial arrangement with 2 repetitions under a Completely Random Blocks Design (DBCA), where the factors were: Factor A (cassava conditioning process), factor B (fermentation agents) and factor C (percentages of fermentative agents at 5 and 15%), obtaining 12 treatments. The variables responses: pH, acidity, ° Brix and alcoholic degrees; data taken every 6 hours for 3 days. Statistical analysis of the data obtained was performed using the Infostat software. It was determined that the best treatments compared to chichas witnessed the white chicha with 15% yeast with a pH 4.51, titratable acidity of 0.64%, 10 ° Brix and 5.6% alcoholic degrees. For chicha wiwis with 5% kefir with a pH of 3.97, titratable acidity at 0.68%, Brix ° of 17.95 and alcoholic degrees of 9.8%. Finally, for chicha negra with 5% yeast with a pH of 4.22, titratable acidity of 0.71%, Brix ° of 10.79 and alcoholic degrees of 5.95. An analysis of the physical-chemical characteristics of the best treatments such as turbidity (UNT), viscosity (cP), reducing sugars (%) and glycerin (g / 100g of anhydrous alcohol) was performed. For the chicha blanca the following results were obtained: 13,800 UNT in turbidity, 969 cP in viscosity, 0.06% reducing sugars and 0.84 g / 100g of anhydrous alcohol for glycerin. For chicha wiwis of 17,050 UNT in turbidity, 5106 cP in viscosity, 0.49% reducing sugars and 12.09 g / 100g of anhydrous alcohol for glycerin. Finally, for chicha negra, results of 21,050 UNT in turbidity, 9890 cP in viscosity, 0.69% reducing sugars and 16.15 g / 100g of anhydrous alcohol for glycerin were obtained. A hedonic sensory analysis was performed showing 30% acceptance of the analyzed attributes of the 3 fermented beverages. It was concluded that the addition of fermentative agents in the established percentages are statistically specific with the controls